SCRAPBOOKING RELATED TO PERSONAL HYGIENE HABITS AND PREVENTION BEHAVIOR OF PATHOLOGICAL LEUCORRHOEA - Hesty Widyasih; Yani Widyastuti (Proceedings of the International Conference on Applied Science and Health, 2019)
Background: Leucorrhoea is the vaginal secretion in term of physiological or pathological. Around 90% of girls in Indonesia have the potential to experience leucorrhoea. Personal hygiene habit is one of the factors that play an important role in avoiding infections that can cause vaginal discharge. Scrapbooking is the art of attaching photos or images on print media and decorating them into creative works. This concept was developed in this study as an alternative media for teenagers to make it easier to remember the health messages. This study aims to determine the effect of scrapbooking on personal hygiene habits and prevention behavior of pathological leucorrhoea for Islamic boarding students (santri). Methodology: The design of this study was a quasi-experimental design with pre-posttest design with control group. The research subjects were 150 female students (75 as a control group and 75 as an experiment group) from the Islamic Boarding School (PP) Ali Maksum Bantul, PP. Salman Al Farisi Sleman and PP. Bina Umat Sleman. Data was analyzed by using univariate and bivariate (paired t-test and independent sample t-test). Results: Most of students have experienced pathological leucorrhoea (80%). Scrapbooking and giving leaflets both have a significant influence on improving personal hygiene habits (p = 0.000) and prevention behavior of pathological leucorrhoea (p = 0.001). There was a scrapbooking effect on personal hygiene habits (p = 0.029) and prevention behavior of pathological leucorrhoea (p = 0.000). Conclusion: There was an effect of scrapbooking on personal hygiene habits and prevention behavior of pathological leucorrhoea. The Boarding school officials can actively participate to motivate students for maintaining personal hygiene through various media that make more interesting. Health workers can use various media to provide counseling about personal hygiene and leucorrhoea prevention. Keywords: Scrapbooking, Personal Hygiene Habits, Leucorrhoea